Microscopy and Antigenic Detection of Trichomonas vaginalis Infections among Female Patients Attending the Gynecology Unit of Dalhatu Araf Specialist Hospital, Lafia. (FULafia Journal of Science and Technology, 2024)
Trichomoniasis is a sexually transmitted infection with a predilection for female urogenital tract and a causative agent for cervicitis, urethritis and vaginalis in women. Trichomonas vaginalis infection is of medical concern amongst women, which, if detected on time, can be treated. The presence and occurrence of Trichomonas vaginalis among female patients attending Dalhatu Araf Specialist Hospital Lafia, Nasarawa State was investigated in this study. Vaginal swab samples of 250 women were collected and examined using wet mount and Laboquick Trichomonas vaginalis antigen test kits. The overall prevalence rate of trichomoniasis was 3.2% among the studied population. The prevalence rate among age group 15-25 years was 5%, 3% in age group 26-35 and 0% among the age group 36-60. Symptomatic and asymptomatic patients exhibited a prevalence rate of 3.9% and 2.06% respectively. Others include; pregnant women with 5.7%, while non-pregnant women recorded 1.8%, students with 5.7%, housewives had 2.8%, traders had 2.5% and 0% prevalence rate was seen among civil servants and farmers respectively. Among the two diagnostic methods used; Laboquick Trichomonas vaginalis antigen test gave the highest prevalence rate of 3.2% compared to wet mount which showed a 1.2% prevalence rate. This demonstrates Laboquick T. vaginalis antigen test kits as a more sensitive and effective diagnostic method in comparison to wet mount. Findings from this study further reiterate the need for more research to enlighten the public on the health implications, control and eradication of this common infection.
Keywords: Trichomoniasis, Trichomonas vaginalis, Laboquick, sexually transmitted infection (STD), Women, Antigenic detection.